Public policy and the education of exceptional children - Nelda H. Cambron (Educational Considerations, 1976)
The 1970s have signaled the advent of a new era for the education of the handicapped child. The public policy arena in which these changes have occurred and will continue to evolve ls the focal point of the Council for Exceptional Children publication titled Public Policy and the Education of Exceptional Children.